Pengembangan Media Pembelajaran Matematika Berbasis Android Menggunakan Adobe Flash CS 6 Pada Materi Trigonometri - Indah Pujiarti; Rosita Dwi Ferdiani; Trija Fayeldi (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2022)
In the era of industrial revolution 4.0 and community technology 5.0, smartphones are currently very widely used by educational practitioners as a medium for learning mathematics. It aims to attract students' interest in learning mathematics that is considered difficult by students such as trigonometry material. A lot of software is used to make android-based learning media for smartphones, one of which is Adobe Flash CS 6. This research is ADDIE version development research which includes five levels, specifically: Analysis, Design, Development, Implementation, and Evaluation. The instruments used are professional validation questionnaires and scholar response questionnaires. The validation expert concludes that Android-based mathematics learning media using Adobe Flash CS 6 on trigonometry material is included in the category